A high-voltage pixel sensor for the ATLAS upgrade - Perić, Ivan; Prathapan, Mridula; Augustin, Heiko; Benoit, Mathieu; Mohr, Raimon Casanova; Dannheim, Dominik; Ehrler, Felix; Messaoud, Fadoua Guezzi; Kiehn, Moritz; Nürnberg, Andreas; Schimassek, Rudolf; Barreto, Mateus Vicente; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2019)
High Voltage CMOS (HVCMOS) pixel sensors have been proposed for upgrade of the ATLAS experiment and for the tracking detectors at future colliders. They are implemented in commercial HVCMOS technologies, which makes the production cost effective when compared to hybrid pixel detectors. The HVCMOS detectors are monolithic, which means that the readout electronics and the sensor part are implemented on the same substrate. A high voltage is used to create a depletion region where the particle detection occurs. A large area prototype for the ATLAS experiment named ”ATLASpix” has been designed and fabricated in the AMS 180nm HVCMOS process technology. ATLASpix includes different design flavors in terms of pixel size and readout logic. HVCMOS pixel sensors have been fabricated using wafers of different resistivity. Design details and measurement results are presented.